The ability to detach from biofilms in the lung airways prior to transmission to another host is associated with the infectious phenotype of Mycobacterium abscessus - Keefe, Bailey; Leestemaker-Palmer, Amy; Bermudez, Luiz E. (Frontiers in Immunology, 2025)
IntroductionMycobacterium abscessus is a pathogen recently associated with patients with chronic lung conditions such as bronchiectasis and cystic fibrosis. M. abscessus is an environmental bacterium but recent evidence suggests that the pathogen is also transmitted from host-to-host. Because M. abscessus is known to form biofilms on the respiratory mucosa the release of bacteria from the biofilm becomes an important aspect on the transmission of the infection.MethodsA biofilm releasing system was established. A transposon library of M. abscessus was then screened to identify genes associated with the release from biofilms.ResultsSeveral enzymes and genes of unidentified function were linked with the ability to detach from the biofilm. It was also shown that detached bacteria were increased capable of establish a new biofilm, attach to epithelial cells, and infect macrophages. To determine the surface molecules linked with the ability to infect new hosts, a surface proteomic was performed, showing that detaching bacteria express many proteins do not present in biofilm bacteria.DiscussionDetached M. abscessus, one of the possible infectious phenotypes, contains specific proteins and lipids in the surface that facilitate the infection of new hosts. In addition, we identified many small proteins that have the likelihood to be associated with the release of the biofilm bacteria.